2009
DOI: 10.1016/j.atherosclerosis.2008.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin induces PON1 expression through p44/42 mitogen-activated protein kinase signaling cascade in Huh7 cells

Abstract: It has been shown that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors have pleiotropic effects and that human serum paraoxonase (PON1) inhibits the oxidative modification of low-density lipoprotein. We investigated the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…We reported that depletion of farnesyl pyrophosphate by pitavastatin was associated with pitavastatin-increased PON1 promoter activity in HepG2 cell [13]; moreover, it was recently reported that pitavastatin also induced PON1 expression through activation of the p44/42 mitogen-activated protein kinase signaling cascade in Huh7 cells [33]. To our best knowledge, it was only one report to refer the association with statins-influenced PKC activity and isoprenoids, which fluvastatin-decreased PKC activity was reversed by isoprenoids [30].…”
Section: Discussionmentioning
confidence: 88%
“…We reported that depletion of farnesyl pyrophosphate by pitavastatin was associated with pitavastatin-increased PON1 promoter activity in HepG2 cell [13]; moreover, it was recently reported that pitavastatin also induced PON1 expression through activation of the p44/42 mitogen-activated protein kinase signaling cascade in Huh7 cells [33]. To our best knowledge, it was only one report to refer the association with statins-influenced PKC activity and isoprenoids, which fluvastatin-decreased PKC activity was reversed by isoprenoids [30].…”
Section: Discussionmentioning
confidence: 88%
“…The consistency among the cellular studies and clinical application affirms the effects of simvastatin treatment, which has the potential to influence antiatherogenic mechanisms at the HDL level, thus providing evidence for one molecular mechanism by which PON expression could be regulated (83). In Huh7 cells, Arii et al found that pitavastatin treatment activates PON1 gene expression and increases PON1 protein expression by increasing the phosphorylation of p44/42 MAP kinases, probably by activating SREBP-2 and Sp1 and increasing their binding to PON1 DNA (18). Pitavastatin can also increase Sp1 binding to PON1 DNA by activating PKC, especially the PKCzeta isoform (17).…”
Section: Pharmacological Modulators Of Ponsmentioning
confidence: 99%
“…Pitavastatin was shown to increase the promoter activity and protein expression of PON1 in vitro. As for the mechanism, pitavastatin was revealed to promote PON1 expression via p44/42 MAP kinase-mediated phosphorylation of SREBP-2 and binding of Sp1 to PON1 DNA 123,124) . The increased PON1 activity was clinically confirmed with the administration of fluvastatin, simvastatin, atorvastatin and rosuvastatin [125][126][127][128] .…”
Section: ) Anti-oxidative Actionmentioning
confidence: 99%